The Anglican Sprituality of Richard Hooker - Grislis, Egis (Toronto journal of theology, 1996)
Within the Anglican tradition there is no one founding patriarch who occupies an exclusively central role. The centre belongs to several and while there is no absolute agreement as to their identity, for the sixteenth century the list includes Thomas Cranmer (1489-1556), John Jewel (1511-1571), Richard Hooker (c. 1554-1600) and Lancelot Andrewes (1555-1626). Among these Hooker stood out as a theologically sophisticated expositor of a via media, a judicious balance between Scripture and tradition, faith and reason, individual responsibility and ecclesial authority. His style was inimitable, his exegesis almost contemporary, and learning universal. To the modern reader Hooker's spelling may initially cause some difficulties, but soon enough is discovered to be helpful, as it assists in savouring Hooker's wisdom and wit. Many of his sentences are epigrammatically brief. Others are long; the longest sentence (in Works, 2.421.32-423.11) has five hundred and thirty words beautifully readable, but not in one breath.